KEPEMIMPINAN KEPALA SEKOLAH DALAM PEMULIHAN DAN TRANSFORMASI PEMBELAJARAN DI LEMBAGA PENDIDIKAN FORMAL - Siswadi Siswadi (STKIP Pesisir Selatan, 2022)
This article examines principal leadership in the recovery and transformation of learning in formal educational institutions post-pandemic. The study uses a qualitative-descriptive approach through a literature review of relevant journal articles, academic books, policy documents, and official reports. The results indicate that principals play a central role not only as administrative managers but also as instructional leaders, transformational leaders, and change agents who direct the school's vision, culture, and quality of learning. In learning recovery, principals coordinate diagnostic assessments, differentiated learning, literacy and numeracy reinforcement, and support for student learning well-being. At the same time, principals lead learning transformation through the integration of digital technology, active-collaborative learning, data-driven evaluation, pedagogical innovation, and strengthening a culture of continuous reflection. The success of this agenda is determined by the principal's managerial and pedagogical competencies, teacher support, the availability of infrastructure, and a willingness to collaborate with parents and the community.